Clinical validation of 13‐gene DNA methylation analysis in oral brushing samples for detection of oral carcinoma: Italian multicenter study. Issue 5 (28th January 2021) - Gissi, Davide B.; Morandi, Luca; Colella, Giuseppe; De Luca, Roberto; Campisi, Giuseppina; Mauceri, Rodolfo; Romeo, Umberto; Tenore, Gianluca; Mignogna, Michele D.; Adamo, Daniela; Oteri, Giacomo; Marcianò, Antonia; et al.
Abstract: Background: The aim of this Italian multicenter study was to evaluate the diagnostic performance of a minimally invasive method for the detection of oral squamous cell carcinoma (OSCC) based on 13‐gene DNA methylation analysis in oral brushing samples. Methods: Oral brushing specimens were collected in 11 oral medicine centers across Italy. Twenty brushing specimens were collected by each center, 10 from patients with OSCC, and 10 from healthy volunteers. DNA methylation analysis was performed in blindness, and each sample was determined as positive or negative based on a predefined cutoff value. Results: DNA amplification failed in 4 of 220 (1.8%) samples. Of the specimens derived from patients with OSCC, 93.6% (103/110) were detected as positive, and 84.9% (90/106) of the samples from healthy volunteers were negative. Conclusion: These data confirmed the diagnostic performance of our novel procedure in a large cohort of brushing specimens collected from 11 different centers and analyzed in blindness.